2004
DOI: 10.1159/000079647
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Differentiated Airway Epithelial Cells to Volatile Smoke in vitro

Abstract: Background: Cigarette smoke (CS) is the predominant pathogenetic factor in the development of chronic bronchitis and chronic obstructive pulmonary disease. The knowledge about the cellular and molecular mechanisms underlying the smoke-induced inflammation in epithelial cells is limited. Objectives: The aim of this study was to develop an in vitro model to monitor the effects of volatile CS on differentiated airway epithelial cells. Methods: The airway epithelial cell line MM-39 and primary human bronchial epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 17 publications
5
61
1
1
Order By: Relevance
“…CS contains more than 4,000 chemicals and additives (22), many of which are volatile. Although in vitro treatment with CSE may not accurately reflect in vivo exposure to CS, reports show that when airway epithelial cells were exposed to volatile CS IL-8 was released into the culture medium via p38 (23). It is well known that neutrophils recruited by the action of IL-8 release NE.…”
Section: Discussionmentioning
confidence: 99%
“…CS contains more than 4,000 chemicals and additives (22), many of which are volatile. Although in vitro treatment with CSE may not accurately reflect in vivo exposure to CS, reports show that when airway epithelial cells were exposed to volatile CS IL-8 was released into the culture medium via p38 (23). It is well known that neutrophils recruited by the action of IL-8 release NE.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue cultures were exposed to volatile cigarette smoke (CS) as described previously 17 . Briefly, tissue cultures were exposed to CS for 15 min (= 3 cigarettes).…”
Section: Smoke Exposure and Infection Modelsmentioning
confidence: 99%
“…RNA isolation, reverse transcription, and quantitative PCR were performed as described elsewhere 17 . GAPDH primer (sense, 5'-GAAGGTGAAGGTCGGAGTC-3'; antisense, 5'-GAAGATGGTGATGGGATTTC-3'), hBD-1 primer (sense, 5'-GCCTCAGGTGGTAACTTTCTCA -3'; antisense 5'-GCGTCATTTCTTCTGGTCACT -3'), and hBD-2 primer (sense 5'-TCAGCTCCTGGTGAAGCTC -3'; antisense 5'-GGGCAAAAGACTGGATGACA -3') were purchased from TIB Molbiol (Berlin, Germany).…”
Section: Cytokine Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these chemokines in promoting inflammation has been investigated in vitro and in vivo. Bronchoalveolar lavage (BAL) fluid from COPD patients contains increased neutrophils, TNF-␣, and IL-8 (25,29), whereas we and others have shown that cigarette smoke extract stimulates human lung cells (epithelial cells, fibroblasts, and macrophages) to release IL-8 (3,19,20,30). In mice, MIP-2 is essential for neutrophil recruitment to the lungs following inflammatory injury (22).…”
mentioning
confidence: 99%